Sanitasi Makanan Minuman dan Pemeriksaan Rectal Swab Penjamah Makanan Pada Hotel Arya Duta Medan Dan Hotel The Palace Inn Tahun 2013 - barita goklas saragih; devi nuraini santi; nurmaini * (Lingkungan dan Kesehatan Kerja, 2014)
ABSTRACT According to Minister of RI No.1098/MENKES/VII/2003, about sanitary hygiene requirements of the food and restaurant, food handlers are people who are directly related to food and equipment ranging from preparation, cleaning, processing, transporting to the presentation. Sanitation is an important part of food processing that must be performed well. A food handlers must be of sound mind should be spiritual, not suffering from infectious diseases or as a carrier. One method of medical examination of food handlers is to use a rectal swab test is the examination by smear at around the anus and perianal around. Rectal swab on a 5-star and 2-star hotel to be done, because the 5-star and 2-star hotel providing accommodation services, food and beverage services, and other services for the public. The purpose of the research to find out the drinks and food sanitation hygiene inspection results rectal swab on food handlers at Hotel Arya Duta Medan and The Palace Inn. Type a descriptive study, a population of 12 people. The sampling technique is the total sampling. The results found that the food and beverage hygiene sanitation both at 100 %, of rectal swab for food handlers negative, age < 30 years 11 ( 91.67 % ), 31-50 years 1 person ( 8.33 % ), Education Academy / PT as much as 9 people ( 75 % ) and high School / equivalent 3 people ( 25 % ), male gender 12 people ( 100 % ), food handlers course yes 10 people ( 83.33 % ) and 2 ( 16.67 % ), long working > 4 years 8 people ( 66.67 % ) and 1-4 years of 4 people ( 33.33 % ), routine periodic health examinations performed 12 people. Suggested for hotel manager who becomes the object of research in the management of beverage and food sanitation inspection of the rectal swabs of food handlers in order to maintain the quality and sanitary quality of foods and beverages that meet the health requirements. Keywords : Sanitary Food Beverages, Rectal Swab